PERSEPSI PEMBELAJAR TERHADAP KOSAKATA, PELAFALAN DAN PENGGUNAAN AUDIO VISUAL BERBASIS INSTAGRAM UNTUK PEMBELAJAR BAHASA PRANCIS PEMULA - Reky Ahmad Nur Salim; Diah Vitri Widayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates students’ perceptions of the use of Instagram-based audiovisual materials in learning French as a foreign language at the beginner level. The research focuses on three main aspects: vocabulary acquisition, pronunciation improvement, and the perceived usefulness and ease of use of Instagram as a learning support tool. A descriptive quantitative research design was employed. The participants were 34 students of SMAK YSKI who were enrolled in French language classes. Data were collected through a closed-ended questionnaire using a five-point Likert scale consisting of 30 statements. The collected data were analyzed using descriptive statistical techniques by calculating mean scores to describe students’ perception tendencies. The results indicate that students generally hold positive perceptions toward the use of Instagram in French language learning. The mean score for vocabulary acquisition was 3.16, indicating that Instagram helps students learn and understand new vocabulary through visual, textual, and audio support. The pronunciation aspect obtained a mean score of 3.19, suggesting that audiovisual content on Instagram assists students in modeling correct pronunciation and intonation. The highest mean score was found in the aspect of usefulness and ease of use (3.28), showing that Instagram is perceived as practical, flexible, and easy to use. Overall, the findings suggest that Instagram has strong potential as a supplementary learning medium for beginner French language instruction.